PENGARUH LIKUIDITAS, CASH FLOW, DAN OPERATING CAPACITY TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI - Lisdawati Sianturi (2021)
Financial distress is a financial condition within the company that is facing a decline so that the company's inability to pay off debts to creditors. This study was conducted to test and provide empirical evidence of the effect of liquidity, cash flow and operating capacity on Financial Distress in manufacturing companies on the Indonesia Stock Exchange in the period 2017-2019. The variables used in this study are Liquidity, Cash Flow, and Operating Capacity. The population in this study amounted to 178 manufacturing companies listed on the Indonesia Stock Exchange during 2017 to 2019. The sample selection used the purposive sampling method, namely the determination of the sample based on the specified criteria, so that the number of samples was 79 companies with a total of 237 samples after conducting observations. elimination. The data in this study is secondary data obtained from the annual financial statements through the website www.idx.co.id. The data of this research were collected by using literature study and documentation method. The analysis technique used is logistic regression with SPSS 25 program with a significance level of 5% (0.05). The results of this study show that partially Liquidity, Cash Flow has a significant effect on Financial Distress while Operating Capacity has no significant effect on Financial Distress.